Fatal disseminated paradoxical embolism in inferior sinus venosus atrial septal defect - Ismail, Zul Khairul Azwadi; Sayuti, Khairil Amir; Abdullah, Mohd Shafie (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
Inferior sinus venosus arterial septal defect (ASD) is a rare congenital cardiac anomaly. As with other types of ASDs and patent foramen ovale (PFO), this defect results in arteri-venous shunting with the risk of developing paradoxical embolism (PDE) to the systemic circulation from venous emboli. We report a case of a 67-year-old lady presented to emergency department (ED) with massive pulmonary embolism (PE) and recurrent acute limb ischaemia. On CT pulmonary angiography (CTPA), an incidental finding of inferior sinus venosus ASD was discovered that has caused the PDE. Thrombolysis was administered followed by open mechanical thrombectomy. The patient developed massive lower gastrointestinal bleed post thrombolysis then passed away despite embolization. This case report describes the catastrophic effect of PDE to cause disseminated multisystem thromboembolism. It also emphasizes the importance of early detection of a possible right-to-left shunt in patients presented with recurrent acute limb ischaemia. Transthoracic echocardiography has reduced sensitivity for inferior sinus venosus ASD requiring further assessment with transoesophageal echocardiography in selected cases.